History of Sufism and its stages of development - سمیە نجیب خلیل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
Sufism is a living spiritual theme, where it occupied most religions and schools by itself. The goal of Sufism is to purify the soul of the defects and release it from the cage of the body. Islam has taken a keen interest in this subject, so the mystical heritage has had a profound impact on the literature and the dictionaries of Muslim nations. This research deals with the stages of emergence, development and growth of Islamic Sufism. For this purpose, the history of Sufism has been divided into severalstages, including: (the Ascetic Sufism stage, the stage of mysticism ashki, the philosophical mysticism stage, the stage of literary mysticism). In the shadow of this division, the most important characteristics of each stage were explained.